The direct medical costs of epilepsy in children and young people: a population-based study of health resource utilisation - Ali, Mostafa A. Sayed; Elliott, Rachel A.; Tata, Laila J. (Elsevier, 2014)
We described the health resource utilisation (HRU) and associated direct medical costs of managing epilepsy in children and young people (CYP) using population-level data from the United Kingdom.